2018
DOI: 10.1002/pd.5351
|View full text |Cite
|
Sign up to set email alerts
|

Impact of prenatal diagnosis of complex congenital heart disease on neonatal and infant morbidity and mortality

Abstract: Prenatal diagnosis of complex CHD leads to improved preoperative morbidity, especially in patients with ductal-dependent cardiac anomalies. No survival benefits were noted with prenatal diagnosis of complex CHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
49
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 31 publications
4
49
1
Order By: Relevance
“…Although only 1% of pregnant patients present a CHD, cardiac disease is the main cause of non-obstetric death in these patients. 9,10 The case reported by Gu et al in 2016 is similar to our case because their patient had a subaortic ventricular septal defect diagnosed in the adulthood and also she had an abortion. 18 Drenthen et al demonstrated that female patients with CCHD who received palliative heart surgery or those without any surgical management, therefore, 11% of cases develop heart failure and supraventricular tachyarrhythmias.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Although only 1% of pregnant patients present a CHD, cardiac disease is the main cause of non-obstetric death in these patients. 9,10 The case reported by Gu et al in 2016 is similar to our case because their patient had a subaortic ventricular septal defect diagnosed in the adulthood and also she had an abortion. 18 Drenthen et al demonstrated that female patients with CCHD who received palliative heart surgery or those without any surgical management, therefore, 11% of cases develop heart failure and supraventricular tachyarrhythmias.…”
Section: Discussionsupporting
confidence: 84%
“…9 Pregnancy patients with congenital cardiopathy should undergo a fetal echocardiogram between 18 and 22 weeks of gestational age. 10 The objective of this study is to present the case of a 19-year-old woman with a double outlet of the right ventricle who had 2 pregnancies.…”
mentioning
confidence: 99%
“…Several studies have reported the beneficial impact of prenatal diagnosis and planned peri-partum care on peri-operative outcomes. [17][18][19][20][21][22] In fact, in most high-income countries, this has become the standard of care and prenatal screening of the fetal heart has been made a mandatory component of prenatal ultrasound protocols. 28 In developed countries, newborn cardiac screening using early physical examination and pulse oximetry screening are relatively well established, in contrast to low-middle-income countries.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Several studies from high-income countries have shown the beneficial impact of prenatal diagnosis of critical CHDs in improving peri-operative outcomes. [15][16][17][18][19][20][21][22] However, in low-middle-income countries, prenatal diagnosis of CHD is limited due to lack of awareness, trained personnel, and lack of implementation of standard protocols in the conduct of mid-trimester anomaly scans. 23 Prenatal diagnosis and planned peri-partum care of neonates with critical CHD might potentially emerge as complementary strategy to improving early postnatal diagnosis, stabilization, and transport.…”
mentioning
confidence: 99%
“…Timely detection of CHD has important advantages: it allows for close monitoring during pregnancy, planning the delivery in a centre with the required treatment facilities and it keeps the option of pregnancy termination open for the parents if the diagnosis is made before 24 weeks gestation. Prenatal diagnosis of CHD has shown to increase survival prior to planned cardiac surgery and decreases preoperative morbidity, especially in the case of ductal-dependent lesions 9 10…”
Section: Introductionmentioning
confidence: 99%